ANALISIS KECENDERUNGAN PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR - Yunus Harjito (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2015)
This study aims to predict the effect of audit quality, financial condition, the growth of the company, the previous year's audit opinion, firm size, and a debt-to-equity ratio of the tendency of going-concern audit opinion. In this study, the type of data used is quantitative data with a population of 145 companies listed in the Indonesia Stock Exchange in 2008-2012. The analytical method used is logistic regression analysis with a sample totalling 20 companies were selected based on the purposive sampling method for 5 periods. Based on the analysis it can be concluded that the quality of the audit significant negative effect on the going-concern audit opinion, the financial condition of the company has no significant effect on the going-concern audit opinion, the growth of the company has no significant effect on the going-concern audit opinion, the previous year's audit opinion has no effect significantly to the going-concern audit opinion, the size of the company does not have a significant effect on the going-concern audit opinion, and the debt-to-equity ratio does not significantly influence the going-concern audit opinion.